THE FORECASTING OF RAW MATERIAL INVENTORY IN SUPPORT OF THE CONTINUITY PRODUCTION PROCESS - Antonio E L Nyoko; Ronald P C Fanggidae; Yohanes Y Marawali (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to calculate the prediction of raw material inventory, the Economic Order Quantity (EOQ), safety stock, and reorder point in support of the continuity production process at a fence manufacturer, CV. Moderen Arsiteknis in Kupang city. Data were analyzed from records of the period 2013–2017 that consist of the annual demand of a product in quantity per unit of time (D), product order cost (S), unit cost (C), holding cost per unit as a fraction of product cost (H), and lead time (L). It is calculated from the forecasting of raw material demand and then computed the Economic Order Quantity (EOQ), safety stock, and reorder point for the next 3 years (2018-2020). The computation of demand forecasts, EOQ, safety stock, and reorder points is intended to smooth the continuity of the production process, reduce the risk of raw material shortages, and minimize the ordering cost and holding cost in CV. Modern Arsiteknis was discussed in the results section. Keywords: Forecasting; Economic Order Quantity; Safety Stock; Re-Order Point